Tissue Engineering Material KLD-12 Polypeptide /TGF-β1 the Protective Effect and Mechanism of Nanofiber Gel on Early Intervertebral Disc Degeneration: Tissue Engineering Material KLD-12 Polypeptide /TGF-β1 - Zhao, Yongsheng; Zhang, Min; Li, Qiang; Chen, Xiufu (Cellular and Molecular Biology, 2022)
Intervertebral disc degeneration (IDD) is a common clinical symptom of multifactorial disease. The treatment and expenditure of IDD cause huge economic and psychological harm to patients, and there is no root treatment in the clinic. However, the appearance of tissue engineering materials provides a new idea for the treatment of early IDD. KLD-12 polypeptide material is a new kind of polypeptide scaffold material, which can be used to repair early IDD and TGF-β1Transforming growth factor-1 plays an important role in the proliferation of Intervertebral disc cells and inhibition of inflammatory response. In order to further understand the tissue engineering material kld-12 polypeptide / TGF-β1 the biomechanical properties of nanofiber gel, and to clarify tissue engineering material KLD-12 polypeptide TGF-β1nanofiber gel provides an experimental basis for the protection and mechanism of early IDD. In this paper, tissue engineering material KLD-12 polypeptide /TGF-β1 is mainly studied as the protective effect and mechanism of nanofiber gel on early IDD. In this paper, through the study of the tissue structure of the intervertebral disc, the composition of the nucleus pulposus, annulus fibrosus and cartilage endplate was studied. The objective was to study the relationship between transforming growth factor TGF-β1 and IDD and to understand its important role in the proliferation of intervertebral disc cells and inhibition of inflammatory response. In this paper, we studied the molecular basis of IDD, the main reason is the imbalance of extracellular matrix synthesis and degradation of Intervertebral disc cells, to understand the structural characteristics of cartilage endplate and the composition of Intervertebral disc fibroblasts. In this study, we studied the cell proliferation activity, the ratio of surviving dead cells, the content of glucosaminoglycans, the content of polyproteoglycan and type II collagen in the gel, and studied the protective effect and mechanism of tissue engineering material KLD-12 polypeptide /TGF-β1 nanofiber gel on early IDD. The results showed that kld-12 polypeptide / TGF-β1 was more effective in the proliferation activity of annulus fibrosus cells of nanofiber gel is higher than that of KLD-12 polypeptide/annulus fibroin nanofiber gel. On 2d, the difference in cell proliferation activity was not obvious, KLD-12 polypeptide / TGF- β 1 the fibrous annulus cell proliferation activity of nanofiber gel was 0.796, and the proliferation activity of KLD-12 polypeptide/annulus fibroin nanofiber gel was 0.786. On the 14d, KLD-12 polypeptide / TGF- β 1 the fibrous annulus cell proliferation activity of nanofiber gel was 1.204, and the proliferation activity of KLD-12 polypeptide/annulus fibroin nanofiber gel was 1.034.